2018
DOI: 10.3390/app8010052
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Tuning of Thermoelectric Properties of Ag1−xSb1+xTe2+x (0 ≤ x ≤ 0.4) Alloys

Abstract: Introduction of nonstoichiometry to AgSbTe 2 -based materials is considered to be an effective way to tune thermoelectric properties similarly to extrinsic doping. To prove this postulate, a systematic physicochemical study of the Ag 1−x Sb 1+x Te 2+x alloys (0 ≤ x ≤ 0.4) was performed. In order to investigate the influence of the cooling rate after synthesis on phase composition and thermoelectric performance, slowly cooled and quenched Ag 1−x Sb 1+x Te 2+x alloys (x = 0; 0.1; 0.17; 0.19; 0.3; 0.4) were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, Li 2 Ga 6 Te 10 and Na 2 Ga 6 Te 10 are examples of compounds with M + ions (Li + , Na + ) in which all octahedral voids are occupied . The substitution of atoms in the structural voids can significantly modify the thermal and transport properties of such types of materials. …”
Section: Introductionmentioning
confidence: 99%
“…However, Li 2 Ga 6 Te 10 and Na 2 Ga 6 Te 10 are examples of compounds with M + ions (Li + , Na + ) in which all octahedral voids are occupied . The substitution of atoms in the structural voids can significantly modify the thermal and transport properties of such types of materials. …”
Section: Introductionmentioning
confidence: 99%
“…Recent works are devoted to the search for optimal compositions of this nonstoichiometric phase, which exhibits a high thermoelectric figure of merit. 46,47 The eutectic of the Ag 2 Te-Sb 2 Te 3 system crystallizes at 70 mol% Ag 2 Te and 817 K. 38 The phase diagram of the PbTe-Sb 2 Te 3 boundary system reported in, 48 was characterized by formation only ternary compound Pb 2 Sb 6 Te 11 , at approximately the eutectic composition on peritectic reaction at 860 K. Shelimova et al, 49 showed formation in this system also PbSb 2 Te 4 and PbSb 4 Te 7 compounds with a layered structure. However, further studies on this system, 50,51 have not confirmed the last compounds.…”
Section: Boundary Quasi-binary Systemsmentioning
confidence: 99%
“…24−27 However, in some special systems, such as AgSbTe 2 , due to the intrinsic high σ and low κ l , 28−30 the κ e /κ total ratio is already high enough that when positive doping is applied, though the PF is optimized, the increase in κ e can offset the decrease in κ l and make the κ total increase with the increase of PF, which limits the improvement of thermoelectric performance and may even degrade the final ZT value. 31 This issue urges us to adopt new doping modes that can improve PF while ensuring the effective reduction of κ total . In this regard, the amphoteric doping method that combines positive dopant with additional negative dopant to adjust and optimize the carrier concentration may serve as a satisfactory solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Contrarily, the negative doping mode refers to inverse element doping which has a purpose to decrease the major carrier concentration through charge compensation with the introduced minor carriers. , It is worth noting that, according to the Wiedemann–Franz law, κ e = L σ T , which indicates that in positive doping the κ e will increase with σ, which is detrimental to the promotion of ZT performance. Fortunately, in most cases, due to the low proportion of κ e in the total thermal conductivity (κ total ), this tiny increase in κ e is always compensated by the large decrease in κ l owning to the strong defect-phonon scattering, which finally gives rise to a reduction of κ total . However, in some special systems, such as AgSbTe 2 , due to the intrinsic high σ and low κ l , the κ e /κ total ratio is already high enough that when positive doping is applied, though the PF is optimized, the increase in κ e can offset the decrease in κ l and make the κ total increase with the increase of PF, which limits the improvement of thermoelectric performance and may even degrade the final ZT value . This issue urges us to adopt new doping modes that can improve PF while ensuring the effective reduction of κ total .…”
Section: Introductionmentioning
confidence: 99%